Mass Transmission Regularities in CdTe under Nanosecond Laser Irradiation - Levytskyi, S.M.; Gnatyuk, D.V.; Koba О.V. (Physics and Chemistry of Solid State, 2022)
In this paper, the mechanisms of mass transfer in the In/CdTe system under nanosecond pulsed laser irradiation, which are due to nonstationarity, nonequilibrium, physical and geometric nonlinearity, high speed and simultaneity of various physical processes; in particular, it is a change in the physical state of a solid body, the generation of elastic and shock waves, significant temperature and stress gradients, defect formation, diffusion, and others. The dominant mechanisms and regularities of indium mass transfer in CdTe under nanosecond laser irradiation of the In-CdTe structure have been established.